A tale of two cookies - Calder, Eve (Calder, Eve. Cookie House mystery., 2021)
"Pastry chef Kate McGuire is loving life on the laid-back island of Coral Cay, Florida. As junior partner in a bakery renowned for luscious desserts- especially her cookies- life is pretty sweet. So when an old friend arrives and announces a spur-of-the-moment beach wedding, that's just the icing on the wedding cake. But the groom vanishes right as a television crew descends on the town to film a hot, new realty show. Is there a connection? Is her friend Desiree somehow involved? Or did groom Judson simply get cold feet? The bride and groom were paired better than warm cookies and cold milk, so Kate doesn't buy it. As the show's cast runs amok on the island and the investigation into Judson's disappearance heats up, Kate and her pal Maxi, along with town dog Oliver, will brave the rambunctious world of reality TV and a wedding weekend gone awry, in an all-out effort to find the missing groom."--Page 4 of cover.